Ocorrência e distribuição de contaminantes emergentes na bacia hidrográfica do Rio Jundiaí - São Paulo - Sousa, Diana Nara Ribeiro de (Universidade Federal de São Carlos, 2015)
Three different classes of emerging contaminants were analyzed in surface water samples, suspended particulate matter (SPM) and sediments from the Jundiaí River Basin - SP. The hormones 17-β-estradiol and 17-α-ethinylestradiol were the only compounds that were not detected in the matrices studied. Caffeine was the compound detected with the highest concentrations for water samples, with values up to 25000 μg/L, while in sediment samples and MPS, triclosan was the compound that had the highest concentrations, with 0.90 μg/g 79.1 g/g, respectively. Other compounds more often detected included atenolol, carbamazepine, diclofenac, propranolol and triclosan, with mean concentrations up to 17 ng/L in samples from Piraí Creek and greater than 120 ng/L for samples from Jundiaí River. A seasonal effect was observed in the concentrations of the compounds and the higher values for all of these were obtained for samples from a sampling point located downstream of a sewage treatment plant. It was found a high correlation between the concentrations of detected compounds and the electrical conductivity, which allowed suggesting the use of new contamination markers by sewage. The occurrence of studied compounds was widespread among samples from Rio Jundiaí, showing the high level of environmental impact to which this water body is exposed.
Occurrence and distribution of emerging contaminants in the Jundiaí River basin São Paulo
Keywords: Química; Águas superficiais; Material particulado; Sedimentos; Recursos hídricos; Fármacos; Hormônios; Produtos de higiene pessoal; Pharmaceuticals; Hormones; Personal care products; Surface waters; Suspended particulate matter; Freshwater sediments; CIENCIAS EXATAS E DA TERRA::QUIMICA